A new combination in Justicia and a new synonym in Thyrsacanthus results in the restriction of Anisacanthus s.str. (Acanthaceae) to Central and North America - Chagas, Earl Celestino De Oliveira; Costa-Lima, James Lucas Da (Phytotaxa, 2022)
The genus Thyrsacanthus (Acanthaceae) was re-established to accommodate South American species of Anisacanthus recovered as phylogenetically distant from the main Anisacanthus lineage. However, some species of uncertain generic placement remained in Anisacanthus: Anisacanthus pohlii, known only from the type specimen destroyed during World War II; and A. trilobus, recently placed within the New World “justicioid” lineage. In this study, we show A. pohlii to be a later synonym for Thyrsacanthus ramosus and place A. trilobus in Justicia based on macromorphological, palynological, and molecular data. Additionally, lectotypes for the names Drejera ramosa and Anisacanthus pohlii were selected.